Soundings in the Christian Mystical Tradition - Egan, Harvey D. (Book collections on Project MUSE., 2010)
"Called in a special way to listen to God's whispers, the mystics Camplify not only what it means to be baptized into the life, death, and resurrection of Jesus Christ--and having the Trinity live in them--but also what is deepest in the human spirit. Mystics experience themselves as an infinite question to which only God is the answer; as an immense longing that only Love can quench; as a nothing in the face of the No-Thing. They are God's fools, troubadours--the great artists and poets of the interior life whose "learned ignorance" articulates the art of loving God, neighbor, self, the Church, and the world." "In Soundings in the Christian Mystical Tradition Harvey Egan draws on fifty years of reading to sketch the varieties and passion of the mystical life across more than two millennia. Through their stories and words Egan reveals that all were conscious of the paradox of human identity--supremely and unsurpassably manifested in the God-Man--that the genuinely human is disclosed only through surrender to God and that the search for God cannot bypass the genuinely human." ""This is one of the finest books I have ever read on Christian mysticism. Harvey Egan, SJ, with his usual careful scholarship and clear writing style, leads us through the lives of the great Christian mystics in a way that makes mysticism and prayer accessible and inviting even to the most non-saintly among us. Father Egan, a master of the spiritual masters, brings to bear a lifetime of experience and erudition to a topic that can seem far removed from our daily lives but is in fact at its heart: the way we relate to God. I can think of no better introduction to the Christian mystic tradition than Soundings.""--Jacket.